HUBUNGAN PERSEPSI WANITA USIA SUBUR TERHADAP MOTIVASI WANITA USIA SUBUR DALAM MELAKUKAN PEMERIKSAAN PAP SMEAR DI PUSKESMAS HARAPAN RAYA PEKANBARU - asri wahyuni safitri; Susi Erianti; Bayu Saputra (Jurnal Ilmu Keperawatan, 2018)
Pap Smear examination is doing to detect of pre-cancer alteration which possible occurs in cervix. One of the factors of fertile aged women did not do the pap smear examination is not allowed by their husband and embarrassed feeling when examined by male doctors. The family support is very influential to ward the motivation of fertile aged woman to do the pap smear examination. This study aims to determine the relationship between perception and motivation of fertile aged women to do pap smear examination. This was a quantitative study with correlation and cross sectional design. The samples were 100 participants which taken by purposive sampling technique. The data analyzed were used univariate and bivariate with chi-square test. The results showed a part of participants were in 22-35 years old, the education level were senior high school, they are the housewives. There was no relationship between perception and motivasion of fertile aged women to do pap smear examination at region of Harapan Raya public health center in pekanbaru (Pvalue 0,124 > 0,05). It is recommended to Harapan Raya Public Health center to increase the health education about pap smear examination. New psychoanalytic factors I am very idolized and very love my father as much as51 responden (57,30%) biological factor is I feel have character like woman feminim counted 51 respondent.